A Review on Solar Energy Harvesting Wireless Sensor Network - Kaur, Harmandeep; Buttar, Avtar Singh (International Journal of Computer Sciences and Engineering, 2019)
The finite energy of batteries associated with wireless sensor networks is a major constraint which limits its lifetime. One of the methods to overcome this major limitation is energy harvesting systems. Thither are many energy sources available nowadays, but solar energy is flexible, mature and external power source so it is broadly used for energy harvesting in WSN to enhance the life of the network used. This paper presented an overview of solar energy harvesting system and the impact of solar energy harvesting on Wireless Sensor Network. We have also propounded the various energy harvesting sources that are used for WSNs and energy harvesting process. This paper also describes the supercapacitor and various recharging batteries.